Comparative survey of parents\'BMI in obese and non-obese ‎‏6‏‎ - ‎‏12‏‎ year old ‎children in Esfahan, ‎‏2000‏ - nasrin akbari; khosro tavakol; neda parvin; masoumeh delaram; afsaneh kazemiyan (Journal of Holistic Nursing and Midwifery, 2005)
Introduction: Child obesity is an issue which deserves attention because it can cause medical ‎problem in children and adults and it tends to sustain which becomes chronic and causes ‎several health risks in adulthood. In recent years, the increasing prevalence of obesity in ‎children has become an important issue in different parts of world. Therefore diagnosis of ‎child obesity is essential in pediatric.‎ Preventive medicine and the best way are to acknowledge and limit the risk factors.‎